Acute Pancreatitis Associated With Systemic Lupus Erythematosus in a Young Female: A Diagnostic and Therapeutic Challenge - Andres Ordoñes‐Saucedo; Bruno Eduardo Reyes‐Torres; Karen Kortright‐Maldonado; Erika K. Tenorio‐Aguirre; Pedro Rodríguez‐Henríquez; Froylan D. Martínez‐Sánchez (Clinical Case Reports)
ABSTRACT Acute pancreatitis (AP) is a rare but life‐threatening complication in patients with systemic lupus erythematosus (SLE). The case highlights the diagnostic challenges and treatment complexities in managing SLE‐associated pancreatitis. A 20‐year‐old female with a history of SLE presented with acute onset epigastric pain, vomiting, and signs of systemic inflammation. Laboratory findings revealed elevated amylase and lipase levels, confirming AP. Imaging studies showed interstitial edematous pancreatitis and bilateral pleural effusion. The patient was managed with aggressive fluid resuscitation, pain management, and supportive care. A systemic inflammatory response complicated her clinical course, and she required intensive care unit monitoring. This case underscores the importance of early recognition of AP in SLE patients and highlights the need for a multidisciplinary approach to manage this severe complication.